Quaternary ferrites by batch and continuous flow hydrothermal synthesis: a comparison. Issue 44 (22nd October 2019) - Bastianello, Michele; Diodati, Stefano; Dengo, Nicola; McCafferty, Liam; Footer, Charles; Badocco, Denis; Pastore, Paolo; Darr, Jawwad; Gross, Silvia
Abstract : Crystalline spinel quaternary ferrites M x Zn1− x Fe2 O4 (M = Co, Ni) were synthesised through two synthetic routes: conventional batch and continuous flow hydrothermal synthesis. Abstract : Crystalline spinel quaternary ferrites M x Zn1− x Fe2 O4 (M = Co, Ni; x = 0.2, 0.35, 0.5, 0.65, 0.8) were synthesised through conventional batch hydrothermal synthesis (HT) at 135 °C as well as via continuous flow hydrothermal synthesis (CHFS). The as prepared compounds were thoroughly characterised from a compositional (ICP-MS, XPS) and structural (XRD) point of view in order to compare the synthetic approaches and achieve a greater understanding of how the chosen approach influences the characteristics of the resulting spinel.